Pathologies of hyperfamiliarity in dreams, delusions and déjà vu - Gerrans, Philip (Frontiers in Psychology, 2014)
The ability to challenge and revise thoughts prompted by anomalous experiences depends on activity in right dorsolateral prefrontal circuitry. When activity in those circuits is absent or compromised subjects are less likely to make this kind of correction. This appears to be the cause of some delusions of misidentification consequent on experiences of hyperfamiliarity for faces. Comparing the way the mind responds to the experience of hyperfamiliarity in different conditions such as delusions, dreams, pathological and non pathological déjà vu, provides a way to understand claims that delusions and dreams are both states characterized by deficient “reality testing”.